Knowledge and Beliefs about Dengue Transmission and Their Relationship with Prevention Practices in Hermosillo, Sonora - Arellano, Carmen; Castro, Lucía; Díaz-Caravantes, Rolando E.; Ernst, Kacey C.; Hayden, Mary; Reyes-Castro, Pablo (Frontiers in Public Health, 2015)
Background: Dengue is an emerging threat in the U.S.-Mexico border region. Transmission has regularly occurred in Sonora, MX since 1982 but it was not until 2014 that cities directly on the Arizona-Sonora border had local transmission. One of the closest urban areas to have regular seasonal transmission is Hermosillo, SN, MX. Developing a better understanding of the knowledge and perceptions of dengue in close geographic proximity to the border can identify areas to target for prevention and control measures. Methods: We conducted focus groups in six neighborhoods in Hermosillo, SN; three with high dengue transmission and three with lower transmission. Awareness of dengue and experience with dengue was common. Results: In all focus groups discussants reported knowing someone personally who had past dengue infection. We further identified several keys ways that the perceptions of dengue transmission could influence the effectiveness of dengue control campaigns. First, there was confusion about how dengue is transmitted. While people associated dengue with mosquitoes, multiple modes of transmission were perceived including direct person to person transmission. In one focus group discussants indicated a stigma surrounding dengue infection. The necessity to maintain cleanliness in their households was identified as a primary strategy to fight dengue, however, participants also noted the limited impact their actions may have on transmission if there is lack of community support or governmental infrastructure to control neighboring and public spaces. Conclusion: As dengue moves further northward, more efforts should be made to clarify the dynamics of transmission to avoid the development of stigma and more coordinated efforts should be made to not only control but to prevent dengue.